دراسة تأثير درجة الحرارة عمى مستخمص نبات المردقوش )L Majorana Origanum)عمى النشاط المضاد لالكسدة - إيمان, بلحسن; يسرى, بوقطاية; نزيهة, غريسي (My University, 2022)
يف ىذه الدراسة ، مت تقييم املتسخلص االيثانويل لنبات املردقوش الدي يتسخعمل يف الطب الشعيب اجلزائري من حيث الفعالية املضادة لألكتسدة الكصية بواسطة اخخبار DPPH .متت دراسة حركية الخغريات يف عينات املتسخلص املتسلنة عند درجات حرارة خمخصفة )54 ، 45 ، 05 درجة مئوية( عصى مدى ساعة واحدة. أدت زايدة درجة حرارة العالج و زمنو إىل زايدة مجيع العوامل مبا يف ذلك ، نشاط مضادات األكتسدة وتفاوت االرتفاع يف نشاط مضادات األكتسدة ا عصى درجات حرارة الختسلني اعخماد والزمن ، أظهرت النخائج أن كل املتسخلصصات تزيح بشكل معخرب جذر DPPHً ، حيث وجد أن تتسلني متسخلص املردقوش إىل 05 درجة مئوية ملدة 05 دقيقة أكثر فعالية من الختسلني إىل 54 أو 45 درجة مئوية.In this study, the ethanolic extract of the Origanum majorana plant, used in Algerian folk medicine, was evaluated in terms of total antioxidant activity by the DPPH test. The kinetics of changes in Origanum majorana samples heated at different temperatures (45, 50, and 60 °C) over one hour were studied. The results showed that increasing the treatment temperature and time increased all factors, including, the antioxidant activity and the variation of the rise in the antioxidant activity depending on the heating temperatures and time. The results showed that all extracts significantly displace the DPPH root, as it was found that heating the marjoram extract to 60 degrees Celsius for 30 minutes is more effective than heating to 45 or 50 degrees Celsius.
مذكرة ماستر كيمياء
Keywords: اإلجهاد الخأكتسدي، النبااتت الطبية، مضادات األكتسدة، نبات املردقوش; oxidative stress, medicinal plants, antioxidants, marjoram